Perancangan Media Pembelajaran Informatika Kelas VIII Menggunakan Google Sites di SMPN 1 Padang Gelugur - Siregar, Annisa Fitri; Derta, Sarwo; Musril, Hari Antoni; Okra, Riri (Pusdikra-Publishing.com, 2024)
This research refers to the problems found at SMPN 1 Padang Gelugur. The results of observations and interviews identified a problem, namely that there were teachers using a lecture and question and answer approach, which made students bored and made the lesson less interesting because the media was less interesting. Students also find informatics lessons difficult to understand. This study uses the 4-D research and development method, which consists of four stages: definition; design; development (development); and dissemination. The validity test was carried out by a media expert, material expert and language expert. The validity test obtained a final score of 0.85 with valid criteria; the practicality test obtained a final score of 0.94 with very high criteria; and the effectiveness test was given to twenty students with a final score of 0.80 with high criteria.